Paradigma dan Pemikiran Pendidikan Islam KH. Ahmad Dahlan dan KH. Hasyim Asy’ari - Ansor Azhari Simanungkalit; Januar Januar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The thoughts of KH. Ahmad Dahlan and KH. Hasyim Asy’ari have made significant contributions to the reform of Islamic education in Indonesia, especially in response to the challenges of globalization. Both emphasized the importance of integrating religious and general sciences in the education system. KH. Ahmad Dahlan focused on curriculum reform and modern teaching methods by incorporating secular subjects into Islamic educational institutions. Meanwhile, KH. Hasyim Asy’ari emphasized character building, ethics, and the exemplary role of teachers in education. This study aims to examine and analyze the relevance of their ideas in the context of contemporary Islamic education. The method used is library research with a descriptive-analytical approach. The results show that their thoughts remain highly relevant in shaping an Islamic education system that is rooted in Islamic values while being responsive to modern developments.